Contraste entre amistad clásica y transhumana - Vela Gómez, Patricia (2024)
A person’s social character is at the center of the bonds that s/he establishes throughout their life. The advance of technology allows for new ways to meet various human needs, among them socialization. On the other hand, the new understanding of the person while disregarding limits, such as nature and death, opens the way for a reorientation of one’s being and its relationships. The cultural movement called transhumanism seeks to emancipate humankind from suffering, fragility, and finitude so that s/he can reach super longevity, intelligence, and well-being using biotechnology, nanotechnology, and artificial intelligence. This vision of the improved (enhanced) man, not only breaks with the physical limits of human nature but also promotes a peculiar relationship between man and machines endowed with artificial intelligence. An example of this relationship is Replika, a bot that collects personal information from user interaction to become “another me” or a friend. The present work seeks to analyze the transhumanist proposal, especially as it refers to the application of technology in human relationships, and contrast it with a vision of the love of friendship from a classical anthropological vision. Personal ties allow people to integrate through acting together with others and, also, through the personal donation of a spiritual nature. The new concepts of friendship in the era of transhumanism, require a reflective analysis, to know if the proposal corresponds to the need for love of friendship inserted in the longing of every person.